Dhorbah; Metode Pembelajaran Nahwu Sharaf - Ilham, Mochammad Nafish; Ma’sum, Ali (Prosiding Konferensi Nasional Bahasa Arab, 2024)
The difficulty of learning nahwu sharaf (qawa'id) is due to the complexity of Arabic grammar. Effective learning methods, such as Dhorbah, pay attention to the characteristics of Arabic. This study explores Dhorbah's method by comparing it to other methods. The findings of the study resulted in nahwu sharaf learning needing an MGT approach, modules, syllabus, dictionaries, and creative grammar teaching techniques. The Dhorbah method, developed by BBGA Al-Madhribu at State University of Malang, is structured and effective with a focus on planning, implementation, and evaluation. Its specialty: using Mother Tongue, complete material, systematic and other features.صعوبة تدريس النحو والصرف تسبب بتعقيد قواعد اللغة العربية. طريقة التدريس الفعالة، مثل الضربة، تهتم اهتماما بخصائص اللغة العربية. تستكشف هذه المقالة الطريقة الضربة من خلال مقارنتها بالطرق الأخرى. أسفرت نتائج المقالة عن حاجة تدريس النحو والصرف إلى طريقة MGT والكتاب المدرسي والمقرر الدراسي والقاموس وأسلوب تدريس القواعد الإبداعية. الطريقة الضربة، التي طورتها BBGA Al-Madhribu في جامعة مالانج الحكومية، المنظمة والفعالة مع التركيز على التخطيط والتنفيذ والتقويم. تخصصاتها: استخدام اللغة الأم، والمواد الكاملة، والميزات المنهجية وغيرها.